(untitled) (Journal of the College of Basic Education, 2022)
The current study deals with (some of the problems facing sixth preparatory students from the students’ point of view) as an attempt to extrapolate the students’ problems at this stage and what it can have of negative effects on the student’s excellence and increasing his academic achievement, as the suffering of some students from educational, social and psychological problems..., It leaves a clear impact on the scientific and educational level of the student as well as on the psychological and social level. The field study concluded that the impact of the problems on the students was as follows: